IMPLEMENTATION OF THE QUEUE SYSTEM MODEL [M/M/1]:[GD/∞/∞] IN THE DOCTOR QUEUE SERVICE PROCESS AT JETAK HEALTH CENTER, TUBAN DISTRICT - Ahmad Zaenal Arifin; Anif Khoerul Mustofa (Prodi Matematika FMIPA Unirow Tuban, 2023)
One of the development efforts in the health sector is the availability of quality health services. Patient satisfaction is an indicator of success in providing health services to the community. UPTD. Jetak Health Center is a health unit in Montong District, Tuban Regency, which is located on Jalan KH. Chusnan Ali No. 163 Jetak Village, Montong District, Tuban Regency. Queuing Theory is the Mathematical study of queues or waiting lines. Community Health Center follows the Single Channel-Single Phase or [M/M/1]:[GD/∞/∞] queuing system model with exponentially distributed services. Single Channel-Single Phase Model or [M/M/1]:[GD/∞/∞] on UPTD. Jetak Community Health Center is optimal because the waiting time for patients in the queue is approximately 8.8 minutes, meanwhile the UPTD. Jetak Community Health Center applies a maximum waiting time for outpatients of 15 minutes